2016
DOI: 10.1111/oik.02932
|View full text |Cite
|
Sign up to set email alerts
|

Microhabitat partitioning in seagrass mesograzers is driven by consistent species choices across multiple predator and competitor contexts

Abstract: Explanations for the coexistence of multiple species from the same functional group or taxonomic clade frequently include fine-scale resource partitioning. However, despite the hypothesized importance of niche partitioning, we know relatively little about the underlying mechanisms. For example, differences in resource use may be fixed consequences of organism traits, or they may be achieved via context-dependent behaviors. In this study we investigated mechanisms of microhabitat partitioning using eight specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 50 publications
1
16
0
Order By: Relevance
“…Although these experiments were conducted in lab where environmental context, flow, temperature and predator conditions, might differ from what would normally be experienced in the field, consistency across studies lead us to believe that the results may be robust. For example, the amphipods and isopods have robust habitat preference despite variation in predation risk (Lürig et al ), and the preferences we found for some genotypes over others match those found in other experiments conducted across years and nutrient conditions (Tomas et al ). Thus the basic mechanism likely underlying the consumer– plant diversity interaction (preference differences among grazers) seems consistent.…”
Section: Discussionsupporting
confidence: 85%
“…Although these experiments were conducted in lab where environmental context, flow, temperature and predator conditions, might differ from what would normally be experienced in the field, consistency across studies lead us to believe that the results may be robust. For example, the amphipods and isopods have robust habitat preference despite variation in predation risk (Lürig et al ), and the preferences we found for some genotypes over others match those found in other experiments conducted across years and nutrient conditions (Tomas et al ). Thus the basic mechanism likely underlying the consumer– plant diversity interaction (preference differences among grazers) seems consistent.…”
Section: Discussionsupporting
confidence: 85%
“…However, when fish were present, isopods densities were higher in mesocosms with macrophytes than in macrophyte‐free tanks, suggesting that macrophytes can reduce predation pressure by stickleback (Diehl & Kornijów, ). This could occur because macrophytes generate structural habitat complexity (Kovalenko et al., ; Lürig et al., ; Warfe, Barmuta, & Wotherspoon, ), making it difficult for fish to find and capture any isopods, or because they alter the intensity and heterogeneity of the light environment (Baker & Ball, ; Verweij et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is also possible that both biotic and abiotic environmental differences can interact to affect the distributions of phenotypes and fitness, and their covariance. Macrophytes can generate structural complexity (Kovalenko, Thomaz, & Warfe, ) and affect background coloration (Tavares, Pestana, Rocha, Schiavone, & Guillermo‐Ferreira, ), to which not all prey phenotypes are equally well adapted (Lürig, Best, & Stachowicz, ). Thus, differences in macrophyte cover may affect the strength and direction of selection from predation (Merilaita, Lyytinen, & Mappes, ).…”
Section: Introductionmentioning
confidence: 99%
“…Several amphipods and isopods prefer different microhabitats within eelgrass beds at this site (Lürig et al. ), and the presence of genotypes with different heights, widths, or leaf traits may have influenced invertebrate biomass.…”
Section: Discussionmentioning
confidence: 96%